2008
DOI: 10.1080/13590840802305423
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of oral vitamin C

Abstract: Purpose. To test whether plasma vitamin C levels, following oral doses in supplemented volunteers, are tightly controlled and subject to a maximum in the region of 220 mM L 21 , as suggested by previous researchers for depleted subjects. To determine plasma levels following single, variable-sized doses of standard and liposomal formulations of vitamin C and compare the effects of the different formulations. To determine whether plasma levels above ,280 mM L 21 , which have selectively killed cancer, bacteria o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 15 publications
4
28
0
1
Order By: Relevance
“…The results further demonstrated that AA began to manifest its action as early as 30 min of its administration, corresponding to the time when the transportation lasted 30 min. This finding agreed with the results of the pharmacokinetic study on vitamin C that AA exerts its effects following 30 min of its oral administration in humans (Hickey et al, 2008). The results of this study further showed that AA exerted a hypothermic effect in treated rabbits, which agree with the previous findings of Ayo et al (2005) in pullets and Minka and Ayo (2007b) the adverse effects of road transportation stress in rabbits, and that the vitamin is beneficial when administered to the animals before the commencement of the journey.…”
Section: Discussionsupporting
confidence: 82%
“…The results further demonstrated that AA began to manifest its action as early as 30 min of its administration, corresponding to the time when the transportation lasted 30 min. This finding agreed with the results of the pharmacokinetic study on vitamin C that AA exerts its effects following 30 min of its oral administration in humans (Hickey et al, 2008). The results of this study further showed that AA exerted a hypothermic effect in treated rabbits, which agree with the previous findings of Ayo et al (2005) in pullets and Minka and Ayo (2007b) the adverse effects of road transportation stress in rabbits, and that the vitamin is beneficial when administered to the animals before the commencement of the journey.…”
Section: Discussionsupporting
confidence: 82%
“…Ascorbic acid is a water-soluble antioxidant vitamin, non-toxic, sustainable and readily metabolized by the body of most domestic animals and humans (Hickey et al 2008;Padayatty et al 2003), when administered orally its absorption takes about 30 min (Hickey et al 2008;Pardue et al 1984;Tsao 1997). Thus, ascorbic acid administration in pigs subjected to road transportation during the harmmatan and goats during the hot-dry season in the Northern Guinea Savannah zone of Nigeria has been shown to decrease RBC osmotic fragility and reduced oxidative damage to RBCs Minka and Ayo 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Dodatkowo, jednorazowe dawki powyżej 2 g przy podaniu doustnym mogą działać przeczyszczająco. Zwiększenie wchłaniania przy podaniu doustnym możliwe jest przy zastosowaniu liposomalnej postaci kwasu L(+)-askorbinowego [17]. Uzyskanie znacznie wyższych stężeń o potencjalnym działaniu farmakologicznym w schorzeniach typu reumatoidalnych lub nowotworowych, rzędu milimolowych, jest jednak możliwe tylko w przypadku dożylnego podawania witaminy C [15,18].…”
Section: Zapotrzebowanie Na Witaminę Cunclassified